Components of Exogenous Innovation Barriers in Hotels within Nairobi City, Kenya - Nthiga , Rita W. (African Journal of Education,Science and Technology (AJEST), 2018)
The aim of this paper was to establish and conceptualize parameters that can be used to measure exogenous innovation barriers. It is important to understand useful indicators that can be used to examine the extent to which the barriers can affect different aspects of management in the hotel sector. The study employed descriptive research design and was conducted in Nairobi city. From a target population of 190 front line employees, 127 formed the sample size for the study. Purposive sampling was used to select three five-star rated hotels in Nairobi, then employees in the hotels were stratified into primary and support departments before systematic sampling was used to select the respondents. Primary data was gathered from employees by use of administered questionnaires. Reliability of data was tested using Cronbach’s Alpha resulting in a value above 0.7. Factor analysis reduced the indicators from ten to three. Hence exogenous innovation can be measured using three components namely; change hurdles, administrative obstructions and entrepreneurial blockades.